Modeling and Performance Optimization of Louvered Fin Radiators in Negative Gauge Pressure Condition. Issue 4 (10th February 2022) - Wan, Rui; Liu, Zhen; Wu, Huawei; Cheng, Qingsi; Ding, Huafeng
Abstract: The purpose of this paper is to study the effect of the structural parameters of louvered fin radiators on its thermal‐hydraulic performance, optimize its structural parameters, and improve the performance of louvered fin radiators in negative gauge pressure condition. The thermal calculation model of louvered fin radiator in negative gauge pressure is established. Then, the effects of design variables on thermal‐hydraulic characteristics are investigated. The second generation of nondominated sorting genetic algorithm (NSGA‐II) is applied to optimize the louvered fin heat exchanger in negative gauge pressure environment. Technique for order preference by similarity to an ideal solution is applied to choose the final optimal solution. Numerical simulation of the solution is conducted and the result is compared with literature in order to verify the optimization method. The optimal structural parameters are obtained under constraints. Compared with the original test piece, the heat transfer rate of optimal solution is increased by 7.7%, and total annual cost is reduced by 24.8%. The present paper establishes optimization method of louvered fin radiators in negative gauge pressure condition, the optimization result is superior to the original radiator. The optimization method can be used in the design of radiators operating in negative gauge pressure conditions. Abstract : The second generation of non‐dominated sorting genetic algorithm is applied to optimize the louvered fin heat exchanger in negative gauge pressure environment. Compared with the original test piece, the heat transfer rate of optimal solution is increased by 7.7%, and total annual cost is reduced by 24.8%. The optimization method can be used in the design of louvered fin radiators.